PENGARUH UKURAN PERUSAHAAN, KEBIJAKAN HUTANG, KEBIJAKAN DIVIDEN DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN - Mey Wulandani, 12.05.51.0166; ., Sri Sudarsi (Students Journal of Economic and Management, 2016)
The objective of the study is to examine the effect of Firm Size, Debt Policy, Dividend Policy and Profitability of the Firm Value. The research was conducted on an industrial manufacturing company that went public in Indonesia Stock Exchange.The sampling method in this study using purposive sampling method with the research period 2010 to 2013. The data used in this study is data from manufacturing companies that met the selection criteria. The analytical method used in this research was multiple regression analysis.The research proves that the firm size, dividend policies and profitability is significant positive effect on firm value, while the dept policy is unsignificant negative effect on firm value. Adjusted R square value is 0.938 it explains 93.8% of dependent variable can be explained by the independent variable, while the remaining 6.2% is explained by other causes outside the model. Keywords: Firm Value, Firm Size, Debt Policy, Dividend Policy andÂ  Profitability